EFEKTIFITAS TERAPI GENGGAM JARI EFEKTIFITAS TERAPI GENGGAM JARI DAN AKUPRESUR TERHADAP PENURUNAN TEKANAN DARAH LANSIA DI POSYANDU DESA MANGUNAN KECAMATAN KABUH KABUPATEN JOMBANG: DI POSYANDU DESA MANGUNAN KECAMATAN KABUH KABUPATEN JOMBANG - Nurhayati, Ratna; Sugiarto, Kresna Bagus; Effendi, Zainudin; Fatoni, Imam (LPPM STIKes Bahrul Ulum Jombang, 2023)
The design in this study used a two-group pre-experimental comparative design method (two-group pre-post test design). Consisting of 35 populations, a sample of 20 people, using quota simple random sampling technique, the independent variable is finger grip therapy and acupressure, and the dependent variable is blood pressure, and uses the Wilcoxon Signe Ranks Test analysis. The results showed that in group 1 the blood pressure before finger gripping therapy was on average 140-159 diastole 90-99 mmHg and after systolic 120-139 diastole averaged 80-89 mmHg, in group 2 the blood pressure before systolic acupressure was averaged average 140-159 diastole 90-99 mmHg and after systole 120 diastole average 80 mmHg. The results of the statistical test showed that group 1 finger grip therapy and group 2 acupressure had the same p value in the Sig column. (2-tailed) is 0.005 Then p <0.05 so it can be concluded that H1 is accepted, meaning that there is an effectiveness of finger gripping therapy and acupressure on reducing blood pressure, so that finger gripping therapy and acupressure are effective in reducing blood pressure in the Elderly Posyandu, Mangunan Village, Kabuh District Jombang Regency.